Dampak Pemindahan Ibu Kota Negara (IKN) Terhadap Social Security dalam Perspektif Kitab Nitisastra - Angga Dwi Saputra; Gede Agus Siswadi (Samsara Institute Publisher, 2026)
In Indonesia, various factors have been considered in the decision to relocate the National Capital City (Ibu Kota Negara/IKN). These include social, economic, political, cultural, defense and security considerations, as well as vulnerability to natural disasters. Socio-economic and demographic disparities have become one of the main driving forces behind the plan to relocate Indonesia’s capital. The relocation of the capital outside Java is intended to reduce the severe ecological burden currently borne by Jakarta, including overpopulation, traffic congestion, air pollution, and deteriorating water quality. However, relocating a capital city is not an easy undertaking because the capital serves as the primary center of social, economic, and political activities. Therefore, any miscalculation in the relocation process has the potential to create various social and developmental problems. This article aims to examine the impact of the National Capital relocation on social security from the perspective of the Nitisastra text. The study focuses on the implications of the relocation for communities in both the former capital region and the new capital region. The research employs a qualitative method with a historical approach. Data were collected through an extensive review of books, academic journals, news articles, and other relevant literature concerning the relocation of the National Capital. The collected data were then classified according to their respective thematic discussions. The findings indicate that the relocation of the National Capital has the potential to serve as a solution to existing developmental challenges while simultaneously generating positive impacts on social security for communities in both the former capital region (DKI Jakarta) and the new capital region (East Kalimantan).